2020
DOI: 10.1039/d0cc05424k
|View full text |Cite
|
Sign up to set email alerts
|

Ln(ii) amido complexes coordinated by ring-expanded N-heterocyclic carbenes – promising catalysts for olefin hydrophosphination

Abstract: First Ln(ii) ring-expanded NHC complexes (er-NHC)Ln[N(SiMe3)2]2 (Ln = Sm, Yb) are synthesized and proved to be highly efficient pre-catalysts for the intermolecular hydrophosphination of such indolent substrates as 1-alkenes, cyclohexene and norbornene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Numerous transition metals and rare earth metal catalysts have been proficiently utilized for significant hydrophosphination reactions as well as other classes of reactions. 29,[31][32][33][34][35][36][37][38][39][40][41][42][43] The following section presents an overview of reaction strategies with a variety of s-and p-block metal catalysts for C-P bond formation via hydrophosphination, hydrophosphorylation, hydrophosphination and hydrophosphonylation from a variety of unsaturated compounds.…”
Section: Reactions Involving Typical Organophosphorus Substratesmentioning
confidence: 99%
“…Numerous transition metals and rare earth metal catalysts have been proficiently utilized for significant hydrophosphination reactions as well as other classes of reactions. 29,[31][32][33][34][35][36][37][38][39][40][41][42][43] The following section presents an overview of reaction strategies with a variety of s-and p-block metal catalysts for C-P bond formation via hydrophosphination, hydrophosphorylation, hydrophosphination and hydrophosphonylation from a variety of unsaturated compounds.…”
Section: Reactions Involving Typical Organophosphorus Substratesmentioning
confidence: 99%
“…N-heterocyclic carbenes (NHCs) as predominant ligands have found wide application in organometallic chemistry in recent years, and they can be easily modified with different steric and electronic effects. Despite a large number of lanthanide amides with NHCs tethered to anionic groups having been reported, the lanthanide amides stabilized by monodentate neutral NHCs are quite few. , Recently, we have shown that the reactivity and selectivity of the ytterbium bis­(amido) complex Yb­[N­(SiMe 3 ) 2 ] 2 can be significantly improved by combination with NHCs . We reported the series of NHC adducts (I i Pr)­Yb­[N­(SiMe 3 ) 2 ] 2 ( 1Yb ; I i Pr = 1,3-diisopropyl-4,5-dimethylimidazol-2-ylidene), (I i Pr) 2 Yb­[N­(SiMe 3 ) 2 ] 2 ( 2Yb ), (IMe) 2 Yb­[N­(SiMe 3 ) 2 ] 2 ( 3Yb ; IMe = 1,3,4,5-tetramethylimidazol-2-ylidene), and (IMes)­Yb­[N­(SiMe 3 ) 2 ] 2 ( 4Yb ; IMes = 1,3-bis­(2,4,6-trimethylphenyl)­imidazol-2-ylidene), which were applied in the catalytic dehydrogenative coupling of hydrosilanes with amines and catalytic hydrophosphination of alkenes and alkynes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in our work on the reactivity of actinide phosphido complexes, P–H bond activations via σ-bond metathesis are observed, but other mechanisms by which P–H activations occur are less straightforward. Generally, most of these metal-mediated activations involve mononuclear metal complexes, while multimetallic or cooperative examples are limited. , Acquiring further mechanistic insight into these bond activations is important to afford strategies for the functionalization of phosphines, , which are of interest for a wide array of applications. The reactivities of metal alkyl , and hydride complexes, especially with electropositive metals, help to facilitate these bond activations, and thus a number of examples of P–H bond activation are known with f elements, nearly all involving lanthanide complexes. ,, …”
Section: Introductionmentioning
confidence: 99%